1999
DOI: 10.1093/ije/28.4.711
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 18 in Kuwait

Abstract: Trisomy 18 birth prevalence rate is high in Kuwait with advanced maternal age as a significant risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 25 publications
4
23
0
2
Order By: Relevance
“…1,69 APA has not been found to be associated with trisomy 18. 70,71 Fathers of APA were less likely to sire offspring with trisomy 13 and no relationship has been shown between APA and the birth of an offspring with anencephaly or encephalocele. 69 With regard to Klinefelter syndrome, the population risk is around 1 in 500, 72 and one study found this to be increased to 1 in 312 in men of APA .50 years old.…”
Section: Effect Of Paternal Age On Offspring Healthmentioning
confidence: 95%
“…1,69 APA has not been found to be associated with trisomy 18. 70,71 Fathers of APA were less likely to sire offspring with trisomy 13 and no relationship has been shown between APA and the birth of an offspring with anencephaly or encephalocele. 69 With regard to Klinefelter syndrome, the population risk is around 1 in 500, 72 and one study found this to be increased to 1 in 312 in men of APA .50 years old.…”
Section: Effect Of Paternal Age On Offspring Healthmentioning
confidence: 95%
“…The incidence of trisomy 18 in newborns is not affected by paternal age (Naguib et al, 1999), whereas fathers older than 39 years are less likely to have children with trisomy 13 (prevalence ratio 0.4, 95% CI: 0.16 -0.96) in comparison to fathers aged 25-29 years (Archer et al, 2007). Hatch et al (1990) evaluated autosomal trisomies (all autosomes except chromosome 1) in spontaneous miscarriages and found no significant paternal age effects (Hatch et al, 1990).…”
Section: Aneuploidiesmentioning
confidence: 99%
“…Patients with trisomy 18 have prenatal-onset severe growth retardation, characteristic craniofacial features, various visceral and skeletal malformations, and significant psychomotor mental retardation [Carey, 2001]. Several populationbased studies showed a remarkably reduced lifespan, with survival rates at age 1 year from 0 to 10% and with median survival time from 3 to 14.5 days [Carter et al, 1985;Young et al, 1986;Goldstein and Nielsen, 1988;Root and Carey, 1994;Embleton et al, 1996;Naguib et al, 1999;Nembhard et al, 2001;Brewer et al, 2002;Rasmussen et al, 2003]. The major causes of death were reported to be apnea and withdrawal of treatment [Embleton et al, 1996], and the presence of a congenital heart defect did not seem be associated with early death [Embleton et al, 1996;Rasmussen et al, 2003].…”
Section: Introductionmentioning
confidence: 99%